Processing-Structure-Protrusion Relationship of 3-D Cu TSVs: Control at the Atomic Scale - Jinxin Liu (IEEE, 2019)
A phase-field-crystal model is used to investigate the processing-structure-protrusion relationship of blind Cu through-silicon vias (TSVs) at the atomic scale. A higher temperature results in a larger TSV protrusion. Deformation via dislocation motion dominates at temperatures lower than around 300°C, while both diffusional and dislocation creep occur at temperatures greater than around 300°C. TSVs with smaller sidewall roughness $R_{a}$ and wavelength $λ _{a}$ exhibit larger protrusions. Moreover, different protrusion profiles are observed for TSVs with different grain structures. Both protrusions and intrusions are observed when a single grain is placed near the TSV top end, while the top surface protrudes near both edges when it contains more grains. Under symmetric loading, coalescence of the grains occurs near the top end, and a symmetric grain structure can accelerate this process. The strain distributions in TSVs are calculated, and the eigenstrain projection along the vertical direction can be considered an index to predict the TSV protrusion tendency.